Experimental investigations of a new type of fuelling system for heavy-duty diesel engines. (18th March 2009) - Kuszewski, Hubert; Lejda, Kazimierz
This paper presents a new construction for a multi-hole injector as part of a new type of fuelling system for diesel engines, in which the injector needle performs a rotary swinging movement. During fuel injection, the needle changes the area of the atomising orifices. This design changes the shape of atomised fuel sprays and impacts on their properties. The results of experimental investigations of the new type of fuelling system show that fuel sprays formed using a rotary swinging needle injector differ from those generated by a standard injector.